China's Carbon Market: Development, Evaluation, Coordination of Local and National Carbon Markets and Common Prosperity - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2022)
To achieve the commitments to both carbon peaking and carbon neutrality, China should focus on those policies of significant impact on emissions reduction at the lowest cost. Launching the national carbon market with the power generation sector is a good start point in this direction. Since its operation, the carbon price has not experienced sharp fluctuations, and falls within a range of CNY40~60 per ton. The block agreement transaction dominates trading, but with an average discount rate of 9.6% in block agreement, the aforementioned carbon prices overestimate the overall carbon prices. While the overall compliance rate measured against entities reached about 94.4%, there are significant differences across provinces, with compliance rate ranging from 82.9% to a full 100% compliance. Entities engaging in trading are mainly for compliance, and therefore transaction is driven by compliance. This article argues that the development of the carbon market requires further reform of the electricity pricing mechanism and the coordinated development of various related markets. With respect to national carbon trading scheme itself, the article discusses the areas where more work needs to be done to ensure that the national carbon emissions trading scheme functions properly. This involves carbon emissions trading legislation, further improvement in the rules conducive to the use of carbon emissions trading as a market tool, and the expansion of the participating industries and the scope of the carbon market in terms of diversifying market players and increasing trading varieties. Given the co-existence of the national carbon market and regional carbon market pilots, the article suggests the specific areas for the regional carbon markets to take the initiative to strengthen the synergistic effects of national carbon market. Furthermore, the article strongly recommends to continuously increase the proportion of carbon allowances auctions, and to set up a transformation fund from the proceeds of paid allocation of allowances to support the transformation and upgrading of regions with low levels of development and technology in China.
Keywords: Q48; Q53; Q55; Q58; O13; P28; R11; H23; 330; Carbon market; Carbon price; Electricity market; Allowance allocation; Common prosperity